E-046 Safety and efficacy of cangrelor in neurointervention. (4th August 2020) - Ouf, A; ElSayed, S; Musallam, N; Davis, N; Tanprayoon, M; Fifi, J; Mocco, J; Shoirah, H
Abstract : Background: Acute ischemic stroke with tandem cervical and intracranial disease is a morbid entity. Despite the advances in endovascular therapies (EVT), a significant percentage of treated patients develop symptomatic intracranial hemorrhagic conversion. The risk increases with the use of intravenous Glycoprotein IIb/IIIa inhibitors (GPI) during acute stenting. Cangrelor is a novel intravenous P2Y12 inhibitor that has been established as an effective alternative to GPI in cardiac interventions. However, little is known about the safety and efficacy of Cangrelor in neuro-interventions. Methods: This is a series of all cerebrovascular patients treated with EVT in whom Cangrelor was used between January 2019 and August 2019 in a single tertiary center. We describe patient characteristics, technical and pharmacological details and outcomes. Results: Our cohort included 16 patients treated with Cangrelor, 56.3% were male patients, and the median age was 66 years (IQR=18). The majority of patients (75%) were stroke cases, while 3 (18.8%) were diagnosed with aneursyms and 1 (6.3%) received Cangrelor post-op. Out of the 12 stroke patients, 7 patients had a tandem occlusion and 5 patients had intracranial atherosclerotic disease (ICAD) of a single vessel (table 1 ). Standard dosing was used in all patients, with median bolus of 2.36 mg (IQR=0.52) and a median infusion dose of 58.8 mg (IQR=84). Platelet reactivity unit test (PRU) was performed in 7 patients, 10–30 minutes after the bolus dose with a median value of 7 (IQR=63). 62.5% of patients were transitioned to clopidogrel and 25% to ticagrelor. All patients had follow-up vessel imaging 2 days after the procedure. Only 2 patients experienced re-occlusion of their stents while the rest of the stents remained patent. Only 1 patient experienced a symptomatic subarachnoid hemorrhage. Median cost of Cangrelor was 1796 per patient. M, Male; F, female; icad, Intracranial atherosclerotic disease; L, Left; r, right; ica, internal carotid artery; cica, cervical internal carotid artery; va, vertebral artery; m1–3, m1–3 segments of the middle cerebral artery; sah, subarachnoid hemorrhage. Conclusions: Cangrelor has a safer and more effective profile in comparison with GPI in patients undergoing emergent endovascular treatment of cerebrovascular pathologies requiring stenting, particularly patients with tandem occlusion. Further prospective studies are warranted to expand its use in neuro-interventions. Disclosures: A. Ouf: None. S. ElSayed: None. N. Musallam: None. N. Davis: None. M. Tanprayoon: None. J. Fifi: None. J. Mocco: None. H. Shoirah: None.